“Emergent Countries Play, Too!”: The Zeebo Console as a (Partial) Decolonial Project - Paula, Bruno de (Revista Contracampo, 2021)
The present paper discusses questions related to the histories of videogames, more specifically in how we approach videogames in Global South. By using Zeebo, a Brazilian console produced in the late 2000s as an epistemic tool, I discuss the limitations of universalist, mainstream-centric epistemological models for exploring videogames as cultural phenomena. By investigating Zeebo’s discourses about piracy and players in the Global South, I argue that this platform can be seen as a partial decolonial project, destabilising conventional historical narratives about South-North relationships in videogames, but refraining from challenging a mainstream, Global North oriented epistemology. This exploratory work, therefore, elaborates on how a decolonial project of history of videogames, one that is more epistemically just to Global South, could be sought.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 4-Europe (lieu de production du savoir); 5-Créatrice; _Nettoyé

The Gendered Screen: Canadian Women Filmmakers - Austin-Smith, Brenda; Melnyk, George (Wilfrid Laurier University Press, 2010)
Discussions of established women filmmakers whose careers have produced major bodies of work, as well as newer filmmakers and new media artists.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 5-Créatrice; _Nettoyé

"Just Because I'm a Lesbian Doesn't Mean I'm Evolved" The "Bad Queer" Women's Comedic Web Series - San Filippo, Maria (Velvet Light Trap, 2020)
The queer women's comedic web series that have flourished in the last decade, serving as launching pads for their creators, coincided with media-industry nichification's segmentation of a consumer population regarded by advertisers and content providers as one monolithic LGBTQ community. The series I examine-from The Slope, which premiered in 2010, to Strangers, released in 2017-voice their creators' and characters' marginalization from and even opposition to such an imagined community, through recourse to what I call a "bad queer" rhetorical practice, which uses ironic metacommentary to critique assimilationist values and tropes alongside queer identity policing. These series emerged, at least initially, as an alternative sphere of queer media production and a queer discursive mode that employs disidentification as a politicized strategy to challenge dominant LGBTQ scripts. Offering an irreverent alternative to mainstream and millennial LGBTQ cultural products, these "bad queer" web series express the plurality of the queer "community" and expose political contestations within its ranks, and in so doing serve as brand differentiation for a new generation of queer media producers.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Pratiques professionnelles en arts visuels issues de l'autochtonie et de la diversité à Montréal - Uzel, Jean-Philippe; Conseil des arts de Montréal (2017)
Rapport commandé par le Conseil des arts de Montréal
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Indigenous Feature Film Production in Canada: A National and International Perspective - Goulet, Danis; Swanson, Kerry (ImagineNATIVE Film + Media Arts Festival, 2014)
The goal of this research is to examine Aboriginal feature film production in Canada, specifically within the genre of drama. This report documents the rise of Indigenous cinema worldwide and examines Canada's public funding landscape including funding allocations to Aboriginal feature film production from Canada's public funders of film over a five-year period from 2007 to 2012. This report also examines the barriers to feature film production for Aboriginal content creators in Canada, and suggests areas of opportunity that can be targeted in order to boost production in this sector. Aboriginal film production is a relatively young sector, with scarce research existing on the industry. To address this gap in the available information on the sector, the researchers expanded the scope of the study beyond public funding agencies in Canada to include data from public funding agencies in Australia and New Zealand. Aboriginal feature film production in Canada is situated within a global Indigenous cinema context. Australia and New Zealand, in particular, are two pillars of global Indigenous film that offer a realistic point from which to compare Canada's progress. As a result, data from Australia and New Zealand are included in the study, as well as one model in the United States.
Keywords: 1-Cinéma; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

The Routledge Companion to Media Studies and Digital Humanities - Sayers, Jentery (Taylor and Francis, 2018)
"Although the fields of media studies and digital humanities are both well established, their overlaps have not been examined in depth. This comprehensive collection fills that gap, giving students, scholars, and media studies practitioners a cutting-edge guide to understanding the array of methodologies and projects operating at the intersection of digital humanities, computing, and culture. Topics covered include: networks; interfaces; media and culture at scale; procedures, programming, code; memory, digitization, and new media; and hacking, queering, and bending."--Provided by publisher
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Histoire de l'art; _À vérifier-Télé

Game Devs & Others: Tales from the Margins - DePass, Tanya (CRC Press, 2018)
Game Devs & Others: Tales from the Margins tell the true stories of life in the industry by people of color, LGBTQIA and other marginalized identities. This collection of essays give people a chance to tell their stories and to let others know what life on the other side of the screen is like when you’re not part of the supposed “majority”. Key Features This book is perfect for anyone interested in getting into the games industry who feels they have a marginalized identity For those who wish to better diversify their studio or workplace who may or may not have access to individuals that could or would share their stories about the industry Includes initiatives aimed at diversifying the industry that have a positive or negative impact on the ongoing discussions Coverage of ajor news items about diversity, conferences aimed at or having diversity at its core of content and mission are discussed Included essays are written with as little game dev specific jargon as possible, makeing it accessible to people outside the industry as well as those in the scene but that may not have all the insider lingo
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Imagining Indigenous Digital Futures: An Afterword - Raheja, Michelle (Studies in American Indian Literatures, 2017)
In lieu of an abstract, here is a brief excerpt of the content: As I sit writing in my kitchen while the forces of the U.S. military state are brought to bear on thousands of Standing Rock water stewards and land protectors and their allies in Cannonball, North Dakota, I consider how this sail special issue on digital Indigenous studies not only represents a collection of essays about the critical work Indigenous women are performing in their various digital projects but also illustrates that these online “Indigenous territories” (Hearne), crafted on social media platforms such as Twitter and Facebook, save lives. Every single day since the protectors first gathered to oppose the proposed 1,170-mile Dakota Access pipeline (a project that would potentially contaminate the Missouri watershed and the Ogallala Aquifer and desecrate Dakota sacred sites), digital independent and social media have constantly covered the story. At least 1.3 million Facebook users checked in virtually at Oceti Sakowin and other Indigenous camps and communities to ensure that support presence is recognized, while the world monitors the presence of the military and police force gathering at the construction site to curb further violence. The Standing Rock gathering offers hope to networked Indigenous youth, a demographic between three and ten times as likely to commit suicide than the national average peer rate. The Nodapl action in the Indigenous imaginary is an invitation to stand at the front lines of a global movement to protect water and land resources for all living beings on this planet and to draw attention to and support those whose lives and ways of being are in peril through overt military action and consequential environmental destruction. It is also an occasion, in the words of Jolene Rickard, “to invest in the apparatus of the imagination” (Bernardin). One need only look at the online art, handwritten signs, and logos representing #nodapl, #standingrock, [End Page 172] #waterislife, and #rezpectourwater to see the ways in which Indigenous artists are creatively and powerfully envisioning this movement, most often immersed with work that features strong images of Native women and girls, the community backbone and life force. Or we need only view digital videos like computer animator and artist Joseph Erb’s black-and-red graphic history of Standing Rock, “Mni Wiconi / Water Is Life” (https://www.youtube.com/watch?v=kXoy5lzpjiM), and first-person game platforms like Elizabeth LaPensée’s Thunderbird Strike, which extend the conversations at Standing Rock to the struggles over Enbridge’s Alberta tar sands pipeline and fracking practices as players work to undo and prevent further environmental degradation. Following Idle No More’s digital and geospatial (re)articulation of Indigenous territories, we are now living and loving and hoping in this historic moment as new ways of relating to one another and living in deep connection with the land and all its forms of life are being physiologically, intellectually, and spiritually forged at the geospatial confluence of the Missouri and Cannonball Rivers. They are being forged as well through the confluences of digital rivers on our electronic devices and in our online conversations about the beauty and devastation of the events that are unfolding in Standing Rock. Susan Bernardin’s essay in this issue on Heid E. Erdrich’s “Pre-Occupied” considers the meaning of rivers to Native peoples and contends that images of waterways, particularly the Mississippi, are mobilized “to make visible the continuing claims of this and other imperiled riverine systems.” In her introduction, Joanna Hearne asks us, “How might such an intersection of digital and Indigenous specificities take place in a way that is ‘native to the device’; that is, how might Indigenous specificity be embedded in shared platforms that are therefore central to all of our digital lives?” The essays in this special issue respond to this question by theorizing digital media in fresh and innovative ways. Many of us teach digital humanities courses or classes with strong digital media content, but we lack the language for critically engaging this new field on its own terms as it intersects, extends, and radically reconceptualizes more familiar research areas such as cinema studies, Indigenous / Native American studies, communication, literature, art, and history.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

When Rivers Were Trails: Cultural Expression in an Indigenous Video Game - LaPensée, Elizabeth (International Journal of Heritage Studies, 2021)
When Rivers Were Trails is a 2D adventure game wherein The Oregon Trail meets Where the Water Tastes Like Wine through an Indigenous lens. The game depicts a myriad of cultures during the player’s journey from Minnesota to California amidst the impact of land allotment in the 1890s. Initiated by the Indian Land Tenure Foundation, the game was developed in collaboration with the Games for Entertainment and Learning Lab at Michigan State University thanks to support from the San Manuel Band of Mission Indians and the many Indigenous creatives who contributed design, art, music, and writing. Uniquely, When Rivers Were Trails is a sovereign game, meaning that it was directed and informed by Indigenous creatives who maintained the role of final decisions during development. Merging design research and close reading methods, this study sets out to describe the game’s design, development process in regards to the game writing, and the resulting themes which emerged as a result of engaging Indigenous writers in self-determined representations.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Interview with Mira Wardhaningsih from StoryTale Studios on the Indonesian Horror Game Pamali - Trattner, Kathrin; Wardhaningsih, Mira (Gamevironments, 2019)
An interview by Kathrin Trattner with Mira Wardhaningsih, Cultural Content Director from StoryTale Studios about the game Pamali
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Crash Override: How Gamergate (Nearly) Destroyed My Life, and How We Can Win the Fight Against Online Hate - Quinn, Zoë (PublicAffairs, 2017)
You've heard the stories about the dark side of the internet -- hackers, #gamergate, anonymous mobs attacking an unlucky victim, and revenge porn -- but they remain just that: stories. Surely these things would never happen to you. Zoe Quinn used to feel the same way. She is a video game developer whose ex-boyfriend published a crazed blog post cobbled together from private information, half-truths, and outright fictions, along with a rallying cry to the online hordes to go after her. They answered in the form of a so-called movement known as #gamergate--they hacked her accounts; stole nude photos of her; harassed her family, friends, and colleagues; and threatened to rape and murder her. But instead of shrinking into silence as the online mobs wanted her to, she raised her voice and spoke out against this vicious online culture and for making the internet a safer place for everyone. In the years since #gamergate, Quinn has helped thousands of people with her advocacy and online-abuse crisis resource Crash Override Network. From locking down victims' personal accounts to working with tech companies and lawmakers to inform policy, she has firsthand knowledge about every angle of online abuse, what powerful institutions are (and aren't) doing about it, and how we can protect our digital spaces and selves.Crash Override offers an up-close look inside the controversy, threats, and social and cultural battles that started in the far corners of the internet and have since permeated our online lives. Through her story -- as target and as activist -- Quinn provides a human look at the ways the internet impacts our lives and culture, along with practical advice for keeping yourself and others safe online.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des industries culturelles; 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé

Featuring Females: Feminist Analyses of Media - Cole, Ellen; Daniel, Jessica Henderson (American Psychological Association, 2005)
"Featuring Females analyzes the portrayals of women in a variety of outlets, including reality television shows, films, print and electronic news programming, magazines, video games, and commercial advertising. A highly esteemed group of scholars and researchers provides informed, original psychological study, and their thought-provoking findings address the ways in which aging, race/ethnicity, body image, gender roles, sexual orientation and relationships, and violence are treated in the media. Featuring Females is a diverse volume, exploring images and characterizations of women young and old and inspiring discussion of the effects that these representations have on girls, women, and society at large"--
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé; _À analyser; _À vérifier-Cinéma; _À vérifier-Télé

First-Person Encounters #4: Poornima Seetharaman - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we talk with Poornima Seetharaman. She is the first Indian to be inducted in the Women in Games (WIGJ) Hall of Fame and is also the lead game designer at Zynga. Hear as we talk about her foray in the world of gaming.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Critical media studies, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé